Rate-dependent serration behavior of twinning-induced plasticity steel at ultra-low temperature - Taeho Lee; Chetan Singh; You Sub Kim; Dong-Hyun Lee; Jun Hyun Han; Jun-Yun Kang; Soo Yeol Lee (Journal of Materials Research and Technology)
This study investigates the strain rate-dependent deformation behavior of cost-effective twinning-induced plasticity (TWIP) steel, Fe–26Mn-0.4C, at 15 K and reveals intriguing insights into its mechanical properties. The serration type changes from type A to type C with decreasing strain rate, resulting in a quasi-cleavage fracture at the crack initiation site. Microstructural analysis unveils a correlation between strain rate and the evolution of bundle twins, nano-twins, and ε-martensites. These denser networks of deformation twins (DTs) and ε-martensites contribute to impacting the mechanical properties. The mechanism behind the formation of serrations involves a rate-dependent thermal instability effect and the intricate interactions between dislocations and dislocations/Mn–C couples. The distinct findings enhance our understanding of the complex deformation behavior of high-Mn steel at cryogenic temperatures and provide valuable insights into the broader field of high-Mn steel applications in dynamic environments.